An assessment of availability, accessibility and utilization pattern of primary health care services in a rural population of dhanusha district of Nepal. - Yadav, Dipendra Kumar (2008)
ABSTRACT: The concept of primary Health Care has been accepted by all countries as the key to the attainment of "Health for all by 2000AD". It is the first level of contact with the individuals, the families and the community within the national health system, bringing health care as close as possible to where people live. Primary health care is an essential health care. Due to lack of access to quality health care services is most important for improving the health status of the rural people. A cross sectional with the objective of assessment of Availability, Accessibility and Utilization pattern of Primary Health Care Services in a Rural Population of Dhanusha district of Nepal was done. Multi stage random sampling were done to select study subject. The sample consisted of 32 households within 2 kms from health facility and 32 households beyond 2kms from health facility. Total number of persons 391 in 64 households. To sum up it is concludes that the expansion of Primary Health Care system has increased a lot in community, however the utilization of these services is maximum as well as earliest amongst those residing within 2kms radius of Health facility.While as we go farther and farther the utilization rate goes down steadily in quantity and quality both in peripheral / remote regions. Therefore it is essential to augment the health services by taking various measures to improve these deficiencies in Health Care. Present study revealed that satisfactory coverage of health programmes but 22 per cent of population suffered from some health problems that indicated good availability, accessibility and utilization of primary health care services but not good quality of services. It needs further investigation to find out qualities that were provided by health facilities. Services should be augmented and provided through outreach clinics and made uniformity of health services within catchment area. To achieve this if it important to increase and strengthens the IEC activities in the communities being served so that they understand the need utility, importance of various health services components such as medical care, RCH, immunization, family planning and Environment Health.